Perchlorination of Coronene Enhances its Propensity for Self-Assembly on Graphene - Conti, Simone; Del Rosso, Maria G.; Ciesielski, Artur; Weippert, Jurgen; Boettcher, Artur; Shin, Yuyoung; Melinte, Georgian; Ersen, Ovidiu; Casiraghi, Cinzia; Feng, Xinliang; Muellen, Klaus; Kappes, Manfred M.; et al. (ChemPhysChem, 2016)
Providing a quantitative understanding of the thermodynamics involved in molecular adsorption and self-assembly at a nanostructured carbon material is of fundamental importance and finds outstanding applications in the graphene era. Here, we study the effect of edge perchlorination of coronene, which is a prototypical polyaromatic hydrocarbon, on the binding affinity for the basal planes of graphite. First, by comparing the desorption barrier of hydrogenated versus perchlorinated coronene measured by temperature-programmed desorption, we quantify the enhancement of the strength of physisorption at the single-molecule level though chlorine substitution. Then, by a thermodynamic analysis of the corresponding monolayers based on force-field calculations and statistical mechanics, we show that perchlorination decreases the free energy of self-assembly, not only enthalpically (by enhancing the strength of surface binding), but also entropically (by decreasing the surface concentration). The functional advantage of a chemically modulated 2D self-assembly is demonstrated in the context of the molecule-assisted liquid-phase exfoliation of graphite into graphene.
CRIS-Team Scopus Importer:2023-03-20
Keywords: graphene; interfaces; polycyclic aromatic hydrocarbons; self-assembly; statistical thermodynamics